The Contribution of Academic Supervision and Teacher Working Group on Teachers’ Pedagogical Competence - Sirajuddin Saleh; Arismunandar Arismunandar; Anshari Anshari (Universitas Negeri Makassar, 2021)
The purpose of this study was to determine: 1) an overview of the implementation of academic supervision, the Teacher Working Group (KKG), and teachers’ pedagogic competences; 2) The effect of academic supervision and the Teacher Working Group (KKG) on the pedagogical competence of elementary school teachers in Manggala District, Makassar City. This quantitative study was performed in the form of an associative research. The objects of this study were 309 elementary school teachers at 30 schools in Manggala District, Makassar City. Samples were 50% of the total population (155 people) selected using a proportional random sampling technique. Data were collected from questionnaire, observation, and documentation. The obtained data were then analyzed using descriptive statistics and hypotheses were tested based on inferential statistic test. The results of the study showed that: The effectiveness of academic supervision was regarded moderate, while the Teacher Working Group (KKG) was considered effective. In addition, teachers’ pedagogical competence was categorized moderate category. Furthermore, the academic supervision and the Teacher Working Group showed a positive and significant contribution on the pedagogical competence of elementary school teachers in Manggala Kota District Makassar. Thus, it can be concluded that academic supervision activities carried out by school principals and activities carried out in the Teacher Working Group (KKG) forum improved elementary school teachers’ pedagogical competence.